Regression Forest-Based Organ Detection in Normalized PET Images - Fischer, Peter; Daum, Volker; Hahn, Dieter; Prümmer, Marcus; Hornegger, Joachim (Bildverarbeitung für die Medizin 2014, 2014)
The detection of organs from full-body PET images is a challenging task due to the high noise and the limited amount of anatomical information of PET imaging. The knowledge of organ locations can support many clinical applications like image registration or tumor detection. This paper is the first to propose an organ localization framework tailored on the challenges of PET. The algorithm involves intensity normalization, feature extraction and regression forests. Linear and nonlinear intensity normalization methods are compared theoretically and experimentally. From the normalized images, long-range spatial context visual features are extracted. A regression forest predicts the organ bounding boxes. Experiments show that percentile normalization is the best preprocessing method. The algorithm is evaluated on 25 clinical images with a spatial resolution of 5 mm. With 13.8mm mean absolute bounding box error, it achieves state-of-the-art results.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.regres_5